THE INFLUENCE OF UNIQUE PRODUCTS, VIRAL MARKETING, AND CONSUMER REVIEWS ON PURCHASE DECISIONS IN SHOPEE E-COMMERCE FOR SMEs OF PARE CHIPS IN KEDIRI - Anita Sumelvia Dewi; Erwin Syahputra; Umi Nadhiroh; Iing Sri Hardiningrum (Transpublika Publisher, 2024)
The objective of this study is to examine the impact of unique products, viral marketing, and consumer reviews on purchasing decisions in shopee e-commerce for SMEs selling bitter melon chips in Kediri. The research adopts a quantitative approach and includes all consumers who have made purchases from these SMEs through shopee in the last 2 months, resulting in a total of 95 respondents. The data collection process involves the use of questionnaires, and the analysis includes validity and reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis testing. The sampling technique employed in this study is saturated sampling. The research findings indicate that: 1) Unique products do not have a significant impact on purchasing decisions in shopee e-commerce for bitter melon chips SMEs in Kediri, as the significance value is 0.828> 0.05, leading to the rejection of the first hypothesis. 2) Viral marketing has a significant impact on purchasing decisions at bitter melon chip SMEs in Kediri, with a significance value of 0.00 <0.05, supporting the acceptance of the second hypothesis. 3) Consumer reviews also have a significant impact on purchasing decisions for bitter melon chips in Kediri, with a significance value of 0.01 <0.05, confirming the acceptance of the third hypothesis.